2021
DOI: 10.1016/j.ajogmf.2021.100450
|View full text |Cite
|
Sign up to set email alerts
|

Rigor, reproducibility, and transparency of randomized controlled trials in obstetrics and gynecology

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Future trials should be strategized to reduce drop-outs while adopting a longer period of follow-up, preferably up to 1 year after the completion of probiotic treatment. Furthermore, future systematic review should also focus on inclusion of RCTs with larger sample sizes, preferably RCTs whose sample sizes were calculated a priori using statistical power analysis ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future trials should be strategized to reduce drop-outs while adopting a longer period of follow-up, preferably up to 1 year after the completion of probiotic treatment. Furthermore, future systematic review should also focus on inclusion of RCTs with larger sample sizes, preferably RCTs whose sample sizes were calculated a priori using statistical power analysis ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group performed an assessment of CONSORT guideline compliance, and agreement between protocols in pretrial registries and in final publications, in a cross-sectional analysis of 170 OBGYN RCTs published in 6 journals between 2017 and 2019. We found that 80% of trials were compliant (defined as 80% or more checklist items completed) with CONSORT 30. Further, while 98% of trials completed pretrial registration, there were discrepancies between pretrial registry protocols and the final publications in the prespecified primary outcomes (23% discordance), secondary outcomes (68% discordance), and planned sample sizes (40% discordance) 30…”
Section: Lack Of Transparencymentioning
confidence: 93%
“…We found that 80% of trials were compliant (defined as 80% or more checklist items completed) with CONSORT. 30 Further, while 98% of trials completed pretrial registration, there were discrepancies between pretrial registry protocols and the final publications in the prespecified primary outcomes (23% discordance), secondary outcomes (68% discordance), and planned sample sizes (40% discordance). 30 Pretrial registry and reporting guidelines are only beneficial if used.…”
Section: The Value Of Reporting Guidelines and Pretrial Registrationmentioning
confidence: 99%
See 1 more Smart Citation